What are important areas where better technology would support women's health? Findings from a priority setting partnership - Sharon Dixon; Sabrina Keating; Abigail McNiven; George Edwards; Philip Turner; Camilla Knox-Peebles; Neda Taghinejadi; Katy Vincent; Olivia James; Gail Hayward (BMC, 2023)
Abstract Background Women's health has historically lacked investment in research and development. Technologies that enhance women's health ('FemTech') could contribute to improving this. However, there has been little work to understand which priority unmet needs should be a focus for women's health technology development. The voices of clinicians and those who experience and utilise these technologies (including those used at home or encountered in clinical settings) are needed to ensure that device development aligns with need, without risking exacerbating or creating health inequities. Method We undertook a priority setting partnership project exploring unmet needs in women's health and well-being where physical technologies or innovations could help. This comprised gathering feedback from: patients and clinicians using both qualitative surveys and discussions; collating and publishing these responses and asking for feedback; evidence checking unmet needs identified, and holding a partnership priority setting event to agree a top 10 and top 20 list of priorities. Results We generated a 'longlist' of 54 suggestions for areas where better kit, devices or equipment could support women's health. For three, we found evidence of existing technologies which mitigated against that need. We took the remaining 51 suggestions to a partnership priority setting meeting which brought together clinicians and service users. Through discussion as this group, we generated a list of the top 10 areas identified as priorities for technological development and improvement. These included better devices to manage examination, diagnosis and treatment of pelvic pain (including endometriosis), prolapse care, continence (treatment and prevention, related to pregnancy and beyond), menstruation, vaginal pain and vaginismus, point of care tests for common infections, and nipple care when breastfeeding. Conclusion The top priorities suggest far-reaching areas of unmet need across women's life course and across multiple domains of health and well-being, and opportunities where innovation in the devices that people use themselves or encounter in health settings could potentially enhance health and healthcare experiences.